Scrotal Circumference and Its Relationship with Testicular Growth, Age, and Body Weight in Tho Tho (Bos indicus) Bulls. (29th October 2014) - Perumal, P.
Abstract : The present study was undertaken to assess the relationship between the scrotal circumference and testicular parameters with body weight and age in Tho Tho bulls ( Bos indicus ), which were maintained at around the villages of National Research Centre on Mithun (ICAR), Jharnapani, Nagaland, India. A total of 32 Tho Tho bulls were selected and divided into four groups according to their age and each group consisted of 8 bulls, namely, Group I: 18–24 months (n = 8 ), Group II: 25–36 months (n = 8 ), Group III: 37–48 months (n = 8 ), and Group IV: 49 months and above (n = 8 ). The scrotal circumference and testicular parameters were measured with caliper and tape and age of animals was calculated with dental formula. The body weight of bulls was estimated with Shaeffer's formula. Result revealed that the scrotal circumference was highly correlated with testicular parameters and body weight compared to age. Compared to exotic cattle ( Bos taurus ), Tho Tho bull's testicular parameters and scrotal circumference were lower. The results of the present study in Tho Tho bulls revealed that scrotal circumference is a useful indicator and is an important selection criterion to determine the testicular development and breeding soundness in young bulls as it is highly correlated with tesicular parameters.